2007
DOI: 10.1210/en.2007-0454
|View full text |Cite
|
Sign up to set email alerts
|

The Ovine Sexually Dimorphic Nucleus of the Medial Preoptic Area Is Organized Prenatally by Testosterone

Abstract: A sexually dimorphic nucleus that can be identified in adult sheep by its characteristic pattern of cytochrome P450 aromatase mRNA exists in the preoptic/anterior hypothalamic area and is called the ovine sexually dimorphic nucleus (oSDN). In other species, male-typical sexually dimorphic preoptic nuclei develop under the influence of gonadal testosterone exposure. Thus, we hypothesized that the oSDN develops before birth in the sheep and is organized by exposure to testosterone. To test this, we determined wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 66 publications
4
51
0
1
Order By: Relevance
“…Indeed, the volume of the oSDN is already larger in males than in females around day 135 of embryonic life, and treatment of female embryos with testosterone between 30 and 90 days of gestation markedly increases the oSDN volume in these females [49]. These data thus strongly suggest that the volume of the oSDN is determined before birth under the influence of testosterone, in any case well before subjects had an opportunity to express their sexual orientation.…”
Section: (B) Homosexual Sheepmentioning
confidence: 80%
“…Indeed, the volume of the oSDN is already larger in males than in females around day 135 of embryonic life, and treatment of female embryos with testosterone between 30 and 90 days of gestation markedly increases the oSDN volume in these females [49]. These data thus strongly suggest that the volume of the oSDN is determined before birth under the influence of testosterone, in any case well before subjects had an opportunity to express their sexual orientation.…”
Section: (B) Homosexual Sheepmentioning
confidence: 80%
“…In fetuses, PRL mRNA expression appeared to surround the central component of the medial preoptic nucleus. We recently determined that this subnucleus is defined by a distinct pattern of aromatase mRNA expression [25]. This neuroanatomical relationship was readily apparent by superimposing pseudocolored film autoradiograms of PRL and aromatase mRNA expression from adjacent brain sections of the same animal (fig.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that PRL-expressing cells formed a ring around the central component of the medial preoptic nucleus. This nucleus is composed of a group of aromatase-containing neurons and becomes sexually dimorphic by fetal day 135 and is thought to be the nascent ovine sexually dimorphic nucleus [25, 33]. The arrangement of aromatase and PRL expression suggests that locally produced estrogen may be acting in a paracrine fashion to regulate PRL expression.…”
Section: Discussionmentioning
confidence: 99%
“…Even more, differences in size are not linked to testosterone serum concentrations, as the same differences are observed even in castrated adult males treated with testosterone (25) . Other authors (26) reported that female lambs prenatally treated with testosterone had NSD sizes. Even more, ewes treated with androgens during their prenatal stage are less receptive towards males (27) .…”
Section: Diferencias En El Sistema Nervioso Centralmentioning
confidence: 94%
“…Más aún, las diferencias de tamaño no se vinculan con diferencias en las concentraciones séricas de testosterona, manteniéndose las mismas diferencias aún en animales adultos gonadectomizados y tratados con testosterona (25) . También se ha reportado que la exposición a testosterona en el periodo prenatal aumenta el tamaño del NSD de las corderas (26) . Además, las ovejas tratadas con andrógenos durante el periodo prenatal presentan menor comportamiento de receptividad al macho (27) .…”
Section: Diferencias En El Sistema Nervioso Centralunclassified